Preparation method of B, Co-Cu / C catalyst for electrocatalytic NO3RR ammonia synthesis and application of prepared catalyst
By preparing B,Co-Cu/C catalysts, the Faraday efficiency and ammonia yield of electrocatalytic reduction nitrates are improved by using carbon-supported B-Co co-doped Cu nanoparticles, and the complex reaction and low selectivity in the prior art are solved. The problem of efficient ammonia production has been achieved.
Patent Information
- Application Number
- CN202411556469.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-01-07
AI Technical Summary
In the existing electrocatalytic reduction of nitrate ammonia production technology, the polyvalent state of N element leads to complex reactions, the reduction of side reaction water inhibits Faraday efficiency, and the accumulation of nitrite on the surface of Cu catalyst reduces reaction selectivity.
Preparation of B, Co-Cu/C catalysts by forming carbon-supported B-Co co-doped Cu nanoparticles with XC-72R carbon black with CuCl2 and CoCl2 in the presence of NaBH4, it is used to electrocatalyze nitrate reduction reaction and improve the reaction Faraday Efficiency and ammonia yield.
The Faraday efficiency and ammonia yield of NO3RR reaction are significantly improved, providing a low-cost, green and simple electrochemical synthesis ammonia catalyst, and the catalyst has high electrochemical active area and stability.
Smart Images

Figure CN119265611A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrocatalytic ammonia synthesis, and in particular to a method for preparing a B, Co-Cu / C catalyst for electrocatalytic NO3RR ammonia synthesis, a method for preparing carbon-supported B-Co co-doped Cu nanoparticles, and applications of the prepared catalyst. Background Art
[0002] Ammonia is a basic substance in the agricultural and chemical industries and is widely used in the production of fertilizers, medicines, fuels, etc. At present, ammonia is mainly produced through the Haber-Bosch process, which produces ammonia by reacting nitrogen and hydrogen under high temperature and high pressure conditions. Although the Haber-Bosch process is very mature in industry, its high energy consumption and dependence on fossil fuels make this method environmentally and economically challenging. In addition, carbon dioxide emissions generated by the Haber-Bosch process are also one of the important factors leading to global climate change. Therefore, finding a more environmentally friendly and efficient method for producing ammonia has become a hot topic in scientific research.
[0003] At the same time, with the excessive use of nitrogen-containing fertilizers and excessive discharge of industrial wastewater, NO3 in surface water and groundwater has increased significantly. — Concentrations continue to rise, causing serious health hazards and disrupting the global nitrogen cycle. — It is stable and highly soluble in water, so it can remove NO3 from water. — It is a huge challenge.
[0004] In recent years, with the development of electrocatalytic technology, electrocatalytic reduction of nitrate to produce ammonia has become an emerging method for ammonia production. This method reduces nitrate to ammonia through electrochemical reaction, and has the advantages of simple operation, mild reaction conditions, and low energy consumption. Electrocatalytic ammonia production can not only reduce dependence on fossil fuels, but also reduce carbon dioxide emissions, with significant environmental benefits.
[0005] The advantage of electrocatalytic ammonia production is that its reaction conditions are mild, high temperature and high pressure are not required, and energy consumption is low. In addition, the process of electrocatalytic ammonia production can utilize electricity generated by renewable energy (such as solar energy and wind energy), further improving its environmental friendliness. Another advantage of electrocatalytic ammonia production is its high reaction selectivity, which can reduce the generation of by-products and improve the yield and efficiency of ammonia.
[0006] However, this method still faces great problems: since the N element has a relatively wide valence range (-3 to +5), the NO3RR process may involve a variety of reaction intermediates and products, resulting in a complex reaction process; at the same time, the main side reaction of this process is the reduction of water, namely the hydrogen evolution reaction (HER), in which water (water molecules, protons or hydroxide ions) obtains electrons to be reduced to hydrogen, which significantly suppresses the Faraday efficiency (FE) of the nitric acid reduction reaction.
[0007] Among the metal catalysts developed for nitric acid reduction to produce ammonia, Cu shows good ability to electrocatalytically reduce nitrate to nitrite, but nitrite will accumulate on its surface for a long time, thereby affecting the subsequent reaction and reducing the selectivity of the reaction. In order to overcome the defects of the prior art, the present invention prepares B, Co-Cu / C catalyst, which significantly improves the FE and ammonia yield of NO3RR reaction, and provides a simple, green and low-cost preparation method for electrochemical synthesis of ammonia catalyst. Summary of the invention
[0008] In order to overcome the above-mentioned deficiencies of the prior art, the present disclosure provides a method for preparing a B, Co-Cu / C catalyst for electrocatalytic NO3RR synthesis of ammonia, a method for preparing carbon-supported B-Co co-doped Cu nanoparticles, and application of the prepared catalyst.
[0009] According to a first aspect of the present disclosure, a method for preparing a B, Co-Cu / C catalyst for electrocatalytic NO3RR ammonia synthesis is provided, and a method for preparing carbon-supported B-Co co-doped Cu nanoparticles is provided, characterized in that the method comprises the following steps:
[0010] 1) Place 2 g of XC-72R carbon black in 50 mL of concentrated nitric acid, stir for 3 hours at 90 °C oil bath temperature, then centrifuge and wash with deionized water until the supernatant is neutral, and finally vacuum dry;
[0011] 2) 50 mg of the vacuum-dried carbon black in step 1) was taken out and added to 30 mL of deionized water, and ultrasonically treated for 40 minutes to obtain a carbon suspension, 0.65 mL of CuCl2 and 0.13 mL of CoCl2 aqueous solution were added to the carbon suspension, and magnetically stirred for 15 minutes to form a uniform mixture, and then 5 mL of NaBH4 solution was added to the uniform mixture, wherein the NaBH4 was 29.4 mg, and magnetically stirred for 40 minutes. The mixture was washed with deionized water and ethanol for multiple times, and placed in a vacuum drying oven after centrifugation to finally obtain B, Co-Cu / C catalyst.
[0012] Preferably, the atomic ratio of B:Co:Cu in the B,Co-Cu / C catalyst is 12.5:15.9:71.6.
[0013] Preferably, the 50 mL of concentrated nitric acid is 9 mol, the 0.65 mL of CuCl2 is 0.1 mol, and the 0.13 mL of CoCl2 is 0.1 mol.
[0014] According to a second aspect of the present disclosure, there is provided an application of a B, Co-Cu / C catalyst for electrocatalytic NO3RR synthesis of ammonia, characterized in that the catalyst is used for electrocatalytic nitrate reduction reaction synthesis of ammonia.
[0015] Preferably, the steps include:
[0016] 1) In an H-type electrolytic cell with a standard three-electrode system, an electrocatalytic nitrate reduction reaction test was performed, wherein the working electrode was carbon paper loaded with B, Co-Cu / C catalyst, the reference electrode was Ag / AgCl, and the counter electrode was a platinum sheet electrode. Before the test, 60 mL of a mixture of 0.1 mol KOH and 50 mmol KNO3 was added to the two chambers of the H-type electrolytic cell as the electrolyte. Before the test, in order to remove the interference of impurity gases in the electrolyte on the reaction, high-purity argon gas was passed into the electrolyte for 30 minutes;
[0017] 2) Record the change of reaction current over time by constant potential chronoamperometry, the potential window of the test is 0~-0.4V versus RHE, the test time is 2 hours, and after the test, collect the cathode electrolyte;
[0018] 3) Using indigo blue spectrophotometry, the NH4 in the collected electrolyte after reaction was tested using a UV-visible spectrophotometer. + The concentration was used to calculate the ammonia yield and Faradaic efficiency of the reaction.
[0019] The technical effects of the present invention are:
[0020] The liquid phase reduction method adopted by the present invention is simple to operate, low in cost, and has the potential for large-scale industrial production. At the same time, the B, Co-Cu / C catalyst elements prepared by the present invention are evenly dispersed, have a high electrochemical active area (ECSA), and show excellent activity and stability in the electrocatalytic NO3RR reaction. At a potential of -0.2V versus RHE, the FE and ammonia yields reached 98.4% and 182.5mg, respectively. NH3 h -1 mg 催化剂 -1 . BRIEF DESCRIPTION OF THE DRAWINGS
[0021] The above and other features, advantages and aspects of the embodiments of the present disclosure will become more apparent with reference to the following detailed description in conjunction with the accompanying drawings. The accompanying drawings are used to better understand the present solution and do not constitute a limitation of the present disclosure. In the accompanying drawings, the same or similar reference numerals represent the same or similar elements, among which:
[0022] Figure 1 B, X-ray diffraction (XRD) pattern of Co-Cu / C catalyst prepared in Example 1;
[0023] Figure 2 The transmission electron microscope (TEM) image of B, Co-Cu / C catalyst prepared in Example 1;
[0024] Figure 3 This is a high-resolution transmission electron microscopy (HRTEM) image of the B, Co-Cu / C catalyst prepared in Example 1;
[0025] Figure 4 The Cu 2p XPS spectra of B, Co-Cu / C prepared in Example 1 and Cu / C catalyst prepared in Comparative Example 1;
[0026] Figure 5 B, Co 2p XPS spectrum of Co-Cu / C catalyst prepared in Example 1;
[0027] Figure 6 B is prepared in Example 1, B 1s XPS spectrum of Co-Cu / C catalyst;
[0028] Figure 7 CV curves of B, Co-Cu / C prepared in Example 1 and Cu / C catalyst prepared in Comparative Example 1 in 0.1 mol KOH+0.05 mol KNO3 electrolyte;
[0029] Figure 8 FE column comparison chart of B, Co-Cu / C and Cu / C catalysts prepared in Example 1 in the electrocatalytic NO3RR reaction;
[0030] Fig. 9 Column comparison chart of ammonia yield of B, Co-Cu / C and Cu / C catalysts prepared in Example 1 in electrocatalytic NO3RR reaction;
[0031] Fig.10 B, Co-Cu / C and Cu / C catalysts prepared in Example 1 in the electrocatalytic NO3RR reaction of NO2 - Faraday efficiency bar graph;
[0032] Fig.11 The B, Co-Cu / C catalyst prepared in Example 1 contains K15 NO3, K 14 Electrocatalytic NO3RR in NO3 and KNO3-free electrolytes 1 H NMR spectrum;
[0033] Fig.12 CV curve of B, Co-Cu / C catalyst prepared in Example 1 at a potential of 0.01 to 0.11 V;
[0034] Fig.13 The CV curve of the Cu / C catalyst prepared in Comparative Example 3 at a potential of 0.01 to 0.11 V;
[0035] Fig.14 The double layer capacitance (C) of the B, Co-Cu / C prepared in Example 1 and the Cu / C catalyst prepared in Comparative Example 1 dl )picture;
[0036] Fig.15 B, a time-current curve of the Co-Cu / C catalyst prepared in Example 1 for 5 hours of continuous testing;
[0037] Fig.16 B, Co-Cu / C catalyst prepared in Example 1, performance diagram after 5 cycle tests;
[0038] Fig.17 B is the XRD spectrum of the Co-Cu / C catalyst prepared in Example 1 after the electrocatalytic NO3RR reaction. DETAILED DESCRIPTION
[0039] In order to make the purpose, technical solution and advantages of the embodiments of the present disclosure clearer, the technical solution in the embodiments of the present disclosure will be clearly and completely described below in conjunction with the drawings in the embodiments of the present disclosure. Obviously, the described embodiments are part of the embodiments of the present disclosure, not all of the embodiments. Based on the embodiments in the present disclosure, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present disclosure.
[0040] Example 1
[0041] 2 g of XC-72R carbon black was placed in 50 mL of concentrated nitric acid, the concentrated nitric acid was 9 mol, stirred at 90 ° C oil bath temperature for 3 hours, and then centrifuged and washed with deionized water until the supernatant was neutral, and finally vacuum dried, 50 mg of pretreated carbon black was weighed and added to 30 mL of deionized water, ultrasonicated for 40 minutes, then, 0.65 mL of CuCl2 (0.1 M) and 0.13 mL of CoCl2 (0.1 M) aqueous solution were added to the carbon suspension, magnetically stirred for 15 minutes to form a uniform mixture, and then 5 mL of NaBH4 solution (29.4 mg) was added to the solution, magnetically stirred for 40 minutes, washed with deionized water and ethanol for many times, centrifuged and placed in a vacuum drying oven, and finally B, Co-Cu / C samples were obtained.
[0042] Comparative Example 1
[0043] First, 50 mg of pretreated carbon black was weighed and added to 30 mL of deionized water, and ultrasonicated for 40 minutes. Then, 0.78 mL of CuCl2 (0.1 M) aqueous solution was added to the carbon suspension, and magnetic stirring was performed for 3 hours to form a uniform mixture. After impregnation, magnetic stirring was performed at 60° overnight until dry. Finally, the mixture was calcined at 300° in a H2 atmosphere for 2 hours, and then cooled naturally to room temperature to obtain a Cu / C catalyst.
[0044] Figure 1 B, XRD pattern of Co-Cu / C catalyst prepared in Example 1. The main diffraction peak at 43.2° corresponds to the (111) crystal plane of Cu (PDF#04-0836), and the slight diffraction peak at 36.4° corresponds to the (111) crystal plane of Cu2O (PDF#05-0667), which is caused by the inevitable oxidation of the surface when the sample is exposed to air.
[0045] The B, Co-Cu / C catalyst prepared in Example 1 was subjected to atomic inductively coupled plasma spectroscopy (ICP) testing. The results showed that the atomic ratio of B:Co:Cu in the B, Co-Cu / C catalyst was 12.5:15.9:71.6.
[0046] Figure 2 TEM image of B, Co-Cu / C catalyst prepared in Example 1. Figure 2 As shown, B, Co-Cu / C nanoparticles are uniformly dispersed on the carrier carbon black, with an average particle size of 12.6 nm. Figure 3 This is the HRTEM image of the B, Co-Cu / C catalyst. From the image, it can be observed that the lattice spacing is 0.214nm, corresponding to the (111) plane of Cu. The interplanar spacing of the Cu (111) plane in B, Co-Cu / C is slightly larger than the standard value, which is caused by the doping of B and Co into the Cu lattice.
[0047] In order to further explore the chemical composition and valence state of B, Co and Cu elements on the catalyst surface, XPS tests were performed on the B, Co-Cu / C catalysts of Example 1 and the Cu / C catalysts of Comparative Example 1. Figure 4 The Cu 2p spectra of B, Co-Cu / C and Cu / C catalysts are shown in Figure 2. It can be seen that the high-resolution Cu 2p XPS spectra of B, Co-Cu / C show two main peaks at 933.3 and 952.9 eV, which can be attributed to Cu + Cu 0 2p 3 / 2 and 2p 1 / 2 , compared with the Cu / C catalyst, it shifted 0.4° toward the direction of high binding energy. This is because the electronegativity of B is higher and the doping of B causes the electron transfer from Cu atoms to B atoms. Figure 5 B, Co 2p spectrum of Co-Cu / C catalyst, the typical characteristic peaks of Co appear in the figure, and the peaks with binding energies of 778.7eV and 780.7eV correspond to Co 0 , 794.5eV and 796.3eV correspond to Co 3+ , 782.1eV and 797.9eV correspond to Co 2+ , indicating that Co was successfully doped into the B,Co-Cu / C catalyst. Figure 6 This is the B1s spectrum of the B, Co-Cu / C catalyst. A characteristic peak of B was found at 192.5 eV, indicating that B was successfully doped into the B, Co-Cu / C catalyst.
[0048] Example 2
[0049] The electrochemical NO3RR ammonia synthesis performance test was carried out using the B, Co-Cu / C prepared in Example 1 and the Cu / C catalyst prepared in Comparative Example 1. The electrocatalytic NO3RR test used an Ivium electrochemical workstation to carry out the reaction in an H-type electrolytic cell. Catalyst-loaded carbon paper was used as the working electrode, the reference electrode was an Ag / AgCl electrode, and the counter electrode was a platinum sheet electrode. Nafion 211 was placed between the two electrolytic cells as a diaphragm, and the electrolyte was 0.1M KOH+0.05M KNO3. Before the test, in order to remove the interference of impurity gases in the electrolyte on the reaction, high-purity argon gas was passed into the electrolyte for 30 minutes. The NO3RR ammonia synthesis test was carried out using the constant voltage timing method, with a voltage range of 0V to -0.4V and a constant voltage test time of 2h. After the reaction is completed, the electrolyte in the cathode chamber is collected for standby use.
[0050] Figure 7CV curves (10 mV s) of the B, Co-Cu / C catalyst prepared in Example 1 and the Cu / C prepared in Comparative Example 1 in 0.1 M KOH+0.05 M KNO3 electrolyte. -1 ). Compared with the Cu / C catalyst, the B,Co-Cu / C catalyst has a larger current density, which means that it has a higher catalytic activity for the NO3RR reaction.
[0051] Example 3
[0052] Spectrophotometric preparation of NH4 using indigo blue + Color developing solution: Weigh 2 g of trisodium citrate, 2 g of salicylic acid and 1.6 g of sodium hydroxide respectively, and fully dissolve them in 40 mL of deionized water to obtain color developing solution a; weigh 2 mL of sodium hypochlorite and fully mix it with 38 mL of deionized water to obtain color developing solution b; weigh 0.15 g of sodium nitroprusside and dissolve it in 15 mL of deionized water to obtain color developing solution c.
[0053] Example 4
[0054] After testing at different voltages for 2 hours, take 2 mL of the electrolyte after NO3RR reaction in Example 2, add 2 mL of color developing solution a, 1 mL of color developing solution b and 0.2 mL of color developing solution c, shake evenly and place in a dark place for 2 hours. After the color development is completed, the absorption peak of the color-developed electrolyte at 657 nm is measured by an ultraviolet spectrophotometer, and the corresponding NH4 + The ammonia yield and FE at different potentials were further calculated.
[0055] Figure 8 , 9 The electrocatalytic NO3RR performance of B, Co-Cu / C prepared in Example 1 and Cu / C prepared in Comparative Example 1 is compared. As can be seen from the figure, the Faraday efficiency and yield of B, Co-Cu / C at each potential are significantly higher than those of Cu / C, indicating that co-doping B and Co into Cu can effectively improve the catalytic performance of electrocatalytic NO3RR. At -0.2 V (RHE), the FE and ammonia yield of B, Co-Cu / C reached 98.4% and 182.5 mg, respectively. NH3 h -1 mg 催化剂 -1 .
[0056] Example 5
[0057] Weigh 40 mg of naphthylethylenediamine hydrochloride and 0.8 g of sulfonamide, measure 2 mL of phosphoric acid (ρ=1.7 g / mL), fully dissolve them in 10 mL of deionized water to obtain color developing solution d.
[0058] Example 6
[0059] After testing at different voltages for 2 hours, take 2 mL of the electrolyte after NO3RR reaction in Example 2, add 0.1 mL of color developing solution d, shake evenly and place in a dark place for 20 minutes. After the color development is completed, use an ultraviolet spectrophotometer to measure the absorption peak of the electrolyte at 540 nm, and then use the fitted standard curve to calculate the corresponding NO2 - concentration, and then calculate the NO2 - FE.
[0060] Fig.10 B, Co-Cu / C catalyst and Cu / C catalyst prepared in Comparative Example 1 under different potentials NO2 - The FE column comparison chart of Cu / C catalyst shows that the NO2 - The FE of the catalysts is significantly greater than that of the B and Co-Cu / C catalysts, indicating that the co-doping of B and Co into Cu can effectively improve the catalyst's catalytic activity towards the intermediate NO2 - The removal ability of B, Co-Cu / C catalyst pair makes it have good selectivity for NH3.
[0061] Example 7
[0062] In order to verify that the final product NH3 comes from the electrocatalytic NO3RR, rather than being interfered by external pollution and other factors, the 1 H isotope labeling method to study the product NH4 of NO3RR + The source of K 15 NO3 was used as the reactant, and the B, Co-Cu / C catalyst prepared in Example 1 was used for testing, and K 14 Comparison of results when NO3 is used as a reactant. Fig.11 B, Co-Cu / C catalyst with K 14 NO3 and K 15 NO3 as a reactant in electrocatalytic NO3RR 1 H NMR spectrum. The results show that K 15 NO3 as reactant 1 The H NMR spectrum shows two characteristic peaks corresponding to 15 NH4 + , and K 14 NO3 as reactant 1 The H NMR spectrum shows three characteristic peaks corresponding to 14 NH4 + In electrolyte without KNO3 1 No characteristic peaks were found in the H NMR spectrum. The above results prove that the obtained NH3 is produced by electrocatalytic NO3RR.
[0063] Example 8
[0064] In order to measure the double layer capacitance (C dl ), 20mV s -1 , 40mV s -1 , 60mV s -1 , 80mV s -1 , 100mV s -1 , 120mV s -1 The test results are as follows: Fig.12 , 13 shown. Fig.14 is the C of the above two catalysts dl The results show that the C of B, Co-Cu / C catalyst dl The value is 6.58mF cm -2 , which is 2.37 times that of the Cu / C catalyst, indicating that the B,Co-Cu / C catalyst has a higher electrochemical active area and therefore has a higher catalytic performance.
[0065] Example 9
[0066] Stability is one of the most important properties of a catalyst. The B, Co-Cu / C catalyst obtained in Example 1 was used to carry out 5 cycle tests. Fig.15 This is the current-time curve of the B, Co-Cu / C catalyst in a 5-hour cyclic electrolysis test at -0.2 V (RHE). It can be seen that the current did not change significantly during the 5 cycle tests, indicating that the B, Co-Cu / C catalyst has good stability. Fig.16 The ammonia yield and FE of B, Co-Cu / C catalyst after 5 cycles. After 5 cycles, the ammonia yield and FE did not decrease significantly, further indicating the excellent cycle stability of B, Co-Cu / C catalyst. Fig.17 This is the XRD spectrum of the B, Co-Cu / C catalyst after the reaction obtained in Example 1. Its diffraction peak has not changed significantly compared with the XRD before the reaction, which proves the stability of the catalyst structure.
[0067] Although the embodiments of the present disclosure have been disclosed above, they are not limited to the applications listed in the specification and the embodiments. For those skilled in the art, the present disclosure may have various modifications and variations. Any changes, modifications, substitutions, combinations, and simplifications made to the present disclosure shall be equivalent replacement methods and shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a B, Co-Cu / C catalyst for electrocatalytic NO3RR ammonia synthesis, characterized in that: The following steps are involved: 1) Place 2 g of XC-72R carbon black in 50 mL of concentrated nitric acid, stir for 3 hours at 90 °C oil bath temperature, then centrifuge and wash with deionized water until the supernatant is neutral, and finally vacuum dry; 2) 50 mg of the vacuum-dried carbon black in step 1) was taken out and added to 30 mL of deionized water, and ultrasonically treated for 40 minutes to obtain a carbon suspension, 0.65 mL of CuCl2 and 0.13 mL of CoCl2 aqueous solution were added to the carbon suspension, and magnetically stirred for 15 minutes to form a uniform mixture, and then 5 mL of NaBH4 solution was added to the uniform mixture, wherein the NaBH4 was 29.4 mg, and magnetically stirred for 40 minutes. The mixture was washed with deionized water and ethanol for multiple times, and placed in a vacuum drying oven after centrifugation to finally obtain B, Co-Cu / C catalyst.
2. The method for preparing the B, Co-Cu / C catalyst for electrocatalytic NO3RR ammonia synthesis according to claim 1, characterized in that: The atomic ratio of B:Co:Cu in the B,Co-Cu / C catalyst is 12.5:15.9:71.
6.
3. The method for preparing the B, Co-Cu / C catalyst for electrocatalytic NO3RR ammonia synthesis according to claim 1, characterized in that: The 50 mL of concentrated nitric acid is 9 mol, the 0.65 mL of CuCl2 is 0.1 mol, and the 0.13 mL of CoCl2 is 0.1 mol.
4. The use of the B, Co-Cu / C catalyst prepared by the preparation method according to claim 1 for electrocatalytic NO3RR ammonia synthesis, characterized in that: The catalyst is used for synthesizing ammonia through electrocatalytic nitrate reduction reaction.
5. The use of the B, Co-Cu / C catalyst for electrocatalytic NO3RR ammonia synthesis prepared by the preparation method according to claim 4, characterized in that: The following steps are involved: 1) In an H-type electrolytic cell with a standard three-electrode system, an electrocatalytic nitrate reduction reaction test was performed, wherein the working electrode was carbon paper loaded with B, Co-Cu / C catalyst, the reference electrode was Ag / AgCl, and the counter electrode was a platinum sheet electrode. Before the test, 60 mL of a mixture of 0.1 mol KOH and 50 mmol KNO3 was added to the two chambers of the H-type electrolytic cell as the electrolyte. Before the test, in order to remove the interference of impurity gases in the electrolyte on the reaction, high-purity argon gas was passed into the electrolyte for 30 minutes; 2) Record the change of reaction current over time by constant potential chronoamperometry, the potential window of the test is 0 to -0.4 V vs RHE, the test time is 2 hours, and after the test, collect the cathode electrolyte; 3) Using indigo blue spectrophotometry, the NH4 in the collected electrolyte after reaction was tested using a UV-visible spectrophotometer. + The concentration was used to calculate the ammonia yield and Faradaic efficiency of the reaction.
Citation Information
Cited By
Preparation method and application of self-supporting cobalt-doped cuprous oxide double-site cathode electrode
CN120138699A
Cobalt hydroxide / copper heterogeneous interface catalyst with oxygen vacancy and application thereof
CN120866863A